Isolation and characterization of ruminal bacteria degrading DHP, the toxic metabolite of mimosine - Chhabra, Arun; Kaur, Jasjit; Malik, R K; Kaur, Harjit (The Indian Journal of Animal Sciences, 2012)
Presence of 3.4 DHP (3-hydroxy-4 (III)-pyridone), a toxic metabolite of the nonprotein amino acid mimosine, in Leucaena leucocephala , a shrub legume with a high protein content and good potential for animal feed, limits its use. However, animals harbouring 3, 4 DHP-degrading ruminal bacteria are able to utilize leucaena as a forage. DHP degrading bacteria were isolated from rumen fluid of a goat fed on leucaena using 3, 4 A medium containing 0.006% FeCl3. After 48 hr of incubation, black colonies were isolated that degraded 80 to 90% of 3, 4 DHP and 2, 3 DHP. Out of 6 selected isolates, 4 were obligatory anaerobic gram-positive cocci (1.2-1.8 mm), while 2 isolates were obligatory anaerobic gram-negative rods. Isolate P-15 degraded 3, 4 DHP completely in a medium containing glucose and peptone. Its morphological and cultural characteristics showed that it belongs to the rumen Streptococci group. Establishing this strain into the rumen of DHP susceptible animals might be a remedy to the toxicity problem in leucaena fed animals.